2009
DOI: 10.1387/ijdb.072421jc
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of morphogenesis - Hox induced organogenesis of the posterior spiracles

Abstract: The posterior spiracle has become one of the best systems to study how Hox genes control morphogenesis. Interaction of Abdominal-B (ABD-B) with dorso ventral and intrasegmental positional information leads to the local activation of ABD-B primary targets in the dorsal region of the eighth abdominal segment (A8). Primary targets pattern the spiracle subdividing it into two broad areas: external stigmatophore vs. internal spiracular chamber precursor cells. Primary targets then activate secondary targets and mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Modulating cell shape is another way to control single or collective cell migration and tissue remodelling, and Hoxb1b has recently been shown to regulate microtubule dynamics during the process of neural tube formation in zebrafish (Zigman et al, 2014). Hox proteins also directly regulate cell shape, cell-to-cell communication and signalling to properly delimit functional and morphological borders between vertebrate hindbrain segments (Prin et al, 2014), and the Drosophila Hox protein Abdominal B (AbdB) has been shown to coordinate the modifications in cell adhesion and cytoskeleton required for cell shape changes and invagination during development of the posterior spiracle, which constitutes the posterior end of the larval respiratory system (Castelli Gair Hombria et al, 2009). Hox proteins can also couple differentiation with morphogenesis, controlling cell fate decisions along differentiation lineages.…”
Section: An Overview Of the Hox Gene Familymentioning
confidence: 99%
“…Modulating cell shape is another way to control single or collective cell migration and tissue remodelling, and Hoxb1b has recently been shown to regulate microtubule dynamics during the process of neural tube formation in zebrafish (Zigman et al, 2014). Hox proteins also directly regulate cell shape, cell-to-cell communication and signalling to properly delimit functional and morphological borders between vertebrate hindbrain segments (Prin et al, 2014), and the Drosophila Hox protein Abdominal B (AbdB) has been shown to coordinate the modifications in cell adhesion and cytoskeleton required for cell shape changes and invagination during development of the posterior spiracle, which constitutes the posterior end of the larval respiratory system (Castelli Gair Hombria et al, 2009). Hox proteins can also couple differentiation with morphogenesis, controlling cell fate decisions along differentiation lineages.…”
Section: An Overview Of the Hox Gene Familymentioning
confidence: 99%
“…A strict hierarchical architecture whereby Hox proteins regulate cellular functions through intermediate genes is probably not a general rule, although in some cases Hox genes seem to follow this regulatory structure ([111]; see below). Nevertheless, even in this case dual regulation, direct and indirect, of some realizator genes, cannot be excluded.…”
Section: Search For the Targetsmentioning
confidence: 99%
“…The role of Hox genes in regulating cell affinities may be mediated also by cadherins. In the posterior spiracles of the embryo, Abd-B regulates the expression of cadherins, which are probably needed to maintain cohesion of the tissue during the morphogenetic movements that results in spiracle development [111, 161]. …”
Section: The Cellular Functionsmentioning
confidence: 99%
See 2 more Smart Citations